FRI0241 HMGB1 Induces Reactive Oxygen Species (ROS)-Dependent Activation of The ER Stress Pathway in C2C12 Myotubes. (15th July 2016) - Lightfoot, A.P.; Morgan, R.S.; Cooper, R.G.
Abstract : Background: The term myositis describes a heterogeneous spectrum of autoimmune diseases, which cause symmetrical proximal muscle weakness and atrophy, and resulting dysfunction. Infiltration of immune cells into muscle has long been regarded as the primary pathological event in myositis. However, the magnitude of inflammatory cell loads often correlates poorly with the levels of detected muscle weakness, so myositis patients often remain weak in the absence of inflammation; while in a murine myositis model muscle weakness may actually precede inflammatory cell infiltrations. Thus, non-immune cell mediated mechanisms, such as those related to ER stress pathway activation, likely play an important role in weakness and atrophy induction, [1]. High-mobility group box protein 1 (HMGB1) is a chromatin protein which is localised outside of the nucleus in myositis, and induces muscle dysfunction and fatigue, via TLR4 signalling, [2, 3]. Given the likely importance of ER stress pathology activation in myositis, and knowledge that HMGB1 can alter ER stress mechanisms and thus induce reactive oxygen species generation (ROS) in non-muscle systems; we wondered whether HMGB1 could induce ROS generation in muscle, and so contribute to ER stress pathway activation, [4]. Objectives: To determine whether antioxidant compounds can ameliorate in vitro HMGB1-induced activation of the ER stress pathway in skeletal muscle. Methods: C2C12 myotubes were treated with rHMGB1 (10ng/ml) without and with (10nM) of the broad-spectrum antioxidant N-acetyl-L-cysteine (NAC) or (5uM) of the mitochondrial-targeted antioxidant SS-31, for a period of 24 hours. Cells were then harvested, RNA-isolated using TRIzol extraction, and cDNA synthesised. Changes in gene expression associated with ER stress pathway activation, mitochondrial function/dynamics and antioxidant defence mechanisms were examined using qPCR. Results: HMGB1 exposure significantly unregulated the gene expression of the ER stress pathway components ATF4, ATF6 and IRE1. Treatment of cells with HMGB1 in the presence of NAC significantly inhibited this expected upregulation of expression of ATF4, ATF6 and IRE1 genes. Treatment with SS-31, a specific scavenger of mitochondria-derived ROS, similarly inhibited upregulation of expression of these genes, but where inhibition was clearly greater than that due to NAC exposure. Conclusions: In myositis, ER stress has been widely implicated in the pathogenesis of non-immune cell mediated weakness and atrophy induction. Our in vitro findings here suggest that HMGB1 plays a role in ER stress pathway activation, and that both broad spectrum and targeted antioxidant interventions can ameliorate this effect. Thus, the development of therapies to selectively inhibit HMGB1 upregulation of ROS, and/or to selectively block pathogenic ROS effects, may represent worthwhile therapeutic avenues to explore to address issues of myositis-induced weakness and atrophy. References: Lightfoot et al. Curr Opin Rheumatol. 2015; 27(6):580–585; Grundtman et al. Faseb J. 2010 Feb; 24(2):570–578; Zong M et al. Annals of the Rheumatic Diseases. 2013 Aug; 72(8):1390–1399; Luo et al. Biochem Bioph Res Co. 2013 Sep 6; 438(4):732–738. Acknowledgement: University of Liverpool and Myositis UK for generous financial support. Disclosure of Interest: None declared